Synthesis and Antimicrobial Activity of Disubstituted Arylphosphoric Diamide - PRABHA, SHASHI; SAXENA, AMITA (Asian Journal of Chemistry, 2010)
Synthetic o-nitro-p-chloro-phenyl phosphoric diamide hydrolyses via neutral and the conjugate acid species, with two rate maxima (2 and 5 M HCl) at 40 (± 0.5)°C in 12 % DMSO-H2O mixture. Specific acid catalysis bimolecular mode and P-N bond fission, all leading to two mechanistic routes of hydrolysis have been established. The special feature is the intervention of the corresponding monoester during acid hydrolysis. Antifungal activity of C-N-P ester has been observed for C. albicans and C. neoformans.